2014
DOI: 10.1016/j.gheart.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The Global Burden of Hemorrhagic Stroke: A Summary of Findings From the GBD 2010 Study

Abstract: This report summarizes the findings of the GBD 2010 (Global Burden of Diseases, Injuries, and Risk Factors) study for hemorrhagic stroke (HS). Multiple databases were searched for relevant studies published between 1990 and 2010. The GBD 2010 study provided standardized estimates of the incidence, mortality, mortality-to-incidence ratios (MIR), and disability-adjusted life years (DALY) lost for HS (including intracerebral hemorrhage and subarachnoid hemorrhage) by age, sex, and income level (high-income countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
134
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 184 publications
(142 citation statements)
references
References 29 publications
5
134
1
2
Order By: Relevance
“…However, the results provided by A.P., which were adjusted for many potential confounders, supported the lower risk of stroke with increasing milk intake making residual confounding unlikely as an explanation for the difference between continents. The difference in results between continents may reflect differences in types of stroke as in Asia hemorrhagic stroke is more common than in Western countries 41. Our results on hemorrhagic stroke, however, did not provide an explanation for the observed heterogeneity.…”
Section: Discussioncontrasting
confidence: 62%
“…However, the results provided by A.P., which were adjusted for many potential confounders, supported the lower risk of stroke with increasing milk intake making residual confounding unlikely as an explanation for the difference between continents. The difference in results between continents may reflect differences in types of stroke as in Asia hemorrhagic stroke is more common than in Western countries 41. Our results on hemorrhagic stroke, however, did not provide an explanation for the observed heterogeneity.…”
Section: Discussioncontrasting
confidence: 62%
“…Our analysis also revealed a consistently greater reduction in both incidence and fatality rates among IS as compared with HS, which seems to differ from observations made in the Global Burden of Disease Study that indicated reductions in both IS and HS. 25,26 Our findings are also consistent with those from many Western countries that also reported considerable reductions in stroke incidence and case fatality over time. 10,15 Although marked reductions in stroke incidence and fatality have been shown for many decades in Japan, these trends seem to be less consistent in other Asian countries.…”
Section: Discussionsupporting
confidence: 89%
“…However, the prevalence of stroke in Thailand is around 2.0%, which was lower than in countries like Singapore, Korea and India [32]. It has been established that the incidence of haemorrhagic stroke is higher amongst Asian populations compared to their Western counterparts [33]. Nevertheless, the Thai population have been found to have the highest proportion of ischaemic strokes amongst East, South and South-East Asian countries [34].…”
Section: Discussionmentioning
confidence: 98%